2013
DOI: 10.14310/horm.2002.1412
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic vs. open abdominal surgery in male pigs: Marked differences in cortisol and catecholamine response depending on the size of surgical incision

Abstract: ObJEcTIVE: Minimally invasive operations, such as laparoscopic cholecystectomy and adrenalectomy, result in a more rapid recovery of normal function, less physiological disturbances and less stress to the organism than similar open operations. The purpose of this study was to determine the stress response associated with minimally invasive abdominal surgery compared to conventional small or large incision laparotomy. METHODs: We compared the responses of the stress hormones cortisol and the catecholamines adre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 33 publications
1
7
0
1
Order By: Relevance
“…A study held by Krikri and his colleagues on male pigs showed that plasma adrenaline and noradrenaline concentrations were significantly lower during laparoscopic cholecystectomies and adrenalectomies than the open surgeries. These results meet ours although it is an experimental animal study with different anesthetic techniques [33]. Our results showed that norepinephrine and epinephrine levels have a similar increase reaching their maximum 2-h after surgery and dropping down afterward in open surgery group.…”
Section: Map ¼ Co â Svrsupporting
confidence: 89%
“…A study held by Krikri and his colleagues on male pigs showed that plasma adrenaline and noradrenaline concentrations were significantly lower during laparoscopic cholecystectomies and adrenalectomies than the open surgeries. These results meet ours although it is an experimental animal study with different anesthetic techniques [33]. Our results showed that norepinephrine and epinephrine levels have a similar increase reaching their maximum 2-h after surgery and dropping down afterward in open surgery group.…”
Section: Map ¼ Co â Svrsupporting
confidence: 89%
“…Surgical stress could cause a spectrum of changes in the body, involving the neuroendocrine, metabolic, immunological, and hematological systems[ 12 ]. The body’s surgical stress response is mainly determined by the surgical wound severity, including the length of the incision in the abdominal wall from the skin to the parietal peritoneum[ 19 ]. The incision of open hepatectomy often exceeds 20 cm, and the surgical stress is thought to be high.…”
Section: Discussionmentioning
confidence: 99%
“…В эксперименте А. Krikri и соавт. [28] концентрация кортизола при открытых и лапароскопических холецистэктомиях не различалась, в то время как при открытой и лапароскопической адреналэктомии различия были достоверными. А. Veenhof и соавт.…”
Section: Discussionunclassified